A Fairer, Safer, and More Just System for All New Yorkers: Domestic Violence and New York Bail Reform - Gutenplan, Hannah (Columbia Journal of Gender and Law, 2021)
On January 1, 2020, bail reform laws went into effect in New York that eliminated cash bail for thousands of defendants across the state. In step with other reforming jurisdictions across the country, New York aimed to ensure that a defendant’s freedom before trial would not be determined by the individual’s ability to pay. Unlike other reforming jurisdictions, however, New York’s bail laws do not include public safety as a legitimate factor for judges to consider when setting release conditions. Some domestic violence advocates have expressed concern for victims’ safety during the pretrial period in domestic violence cases. This Note explores the potential impact of New York’s bail reform laws on domestic violence cases and whether any mitigating measures may be implemented to promote victims’ safety.